2000
DOI: 10.1002/1529-0131(200009)43:9<2110::aid-anr23>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the chondrocyte response to insulin‐like growth factor 1 in aging and osteoarthritis: Studies in a non‐human primate model of naturally occurring disease

Abstract: These results demonstrate a significant age-related decline in the chondrocyte response to IGF-1. The finding that increasing OA score was associated with a reduced response to intact IGF-1 but not des(1-3) IGF-1 suggests a role of increased production of inhibitory IGFBP in OA. Since the cells from older animals had a reduced response to both forms of IGF-1, the mechanism of the reduced response with age cannot be attributed to changes in IGFBP. Age-related changes in IGF receptors or, more likely, age-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
112
0
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 177 publications
(124 citation statements)
references
References 39 publications
9
112
0
3
Order By: Relevance
“…These data support previous work that demonstrates what has been coined a resistance to IGF-1 stimulation with age (14)(15)(16)48). Hsp90 inhibition at the 2 higher concentrations of geldanamycin tested (100 nM and 500 nM) blocked IGF-1-induced COL2A1 expression.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These data support previous work that demonstrates what has been coined a resistance to IGF-1 stimulation with age (14)(15)(16)48). Hsp90 inhibition at the 2 higher concentrations of geldanamycin tested (100 nM and 500 nM) blocked IGF-1-induced COL2A1 expression.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the oldest chondrocytes (mature) had the greatest Hsp90 AS A THERAPEUTIC TARGET FOR DIMINISHED CARTILAGE CATABOLISM IN OAincrease in COL2A1 mRNA expression after exposure to IGF-1. Previous studies suggesting that chondrocytes become nonresponsive to IGF-1 during aging demonstrated significantly less sulfate incorporation into proteoglycans in aged compared with young chondrocytes (15,16). Taken together, these results suggest that either the IGF-1 nonresponsive state is more specific for proteoglycan than collagen synthesis, or that mRNA expression is less sensitive to the effects of aging than to protein synthesis and assembly of the ECM.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Midcoronal sections of the distal femur and proximal tibia were examined. To quantify the degree of OA-like change, toluidine blue-stained sections were scored (0-7 scale, where 0 ϭ normal and 7 ϭ severe damage, as previously described [18]) by a single investigator (CSC) who was blinded to the immunostaining results. The sections used for the study had scores ranging from 0 to 7 (mean 2.2).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Verbruggen et al [38] did not observe any proliferation for 2-to 69-year-old human chondrocytes embedded in agarose, but an increase in donor age correlated with reduced aggrecan synthetic rate and a smaller proportion of large aggregates. Loeser et al [26], by measuring sulfate and proline incorporation in alginate culture, found a mitigated response of macaque chondrocytes to IGF-1 with increasing animal age. Kamada et al [23] observed that primary aged bovine chondrocytes in alginate proliferate less than chondrocytes from young adults, but nonetheless more than fetal chondrocytes.…”
Section: Introductionmentioning
confidence: 99%